Effectiveness of Filter Media Compositions on Water Quality, Growth and Survival Rate of Tilapia (Oreochromis niloticus) Cultured in Recirculation System - Lailiyah, Mamluatul; Harwanto, Dicky; Desrina, Desrina (Journal Omni-Akuatika, 2023)
Market demand for tilapia (Oreochromis niloticus) is increasing every year. This has encouraged aquaculture companies to apply intensive cultivation systems. However, these applications run the risk of increasing waste and decreasing water quality. One strategy to overcome those problems of water quality is to use recirculation aquaculture system. This study aims to determine the effectiveness of filter media composition on water quality, survival rate, and tilapia growth. The average body weight of the fish used was 3.84 ± 0.05 g per individual. A completely random experiment design with three treatments and three replications were applied. The treatments were combination of several filter media with different compositions, namely A (Dacron + 75% nets + 25% sand), B (Dacron + 50% nets + 50% sand) and C (Dacron + 25% nets + 75% sand).The water quality variables measured were pH, DO, temperature, ammonia, and VTR (Volumetric TAN Removal). The survival rate (SR), relative growth rate (RGR). and total amount feed fed (TFF) of fish were also measured. The results showed that the composition of the filter had a significant effect (P<0.05) between treatment. The best VTR was showed in Treatment C with value 54.65 gm-3d-1.Keywords: Tilapia, recirculation, dacron, nets, sand